Multiple Pathways Act Together To Establish Asymmetry of the Ventral Nerve Cord in Caenorhabditis elegans. Issue 4 (21st February 2019) - Taylor, Jesse; Hutter, Harald
Abstract: The central nervous system of most animals is bilaterally symmetrical. Closer observation often reveals some functional or anatomical left–right asymmetries. In the nematode Caenorhabditis elegans, the most obvious asymmetry in the nervous system is found in the ventral nerve cord (VNC), where most axons are in the right axon tract. The asymmetry is established when axons entering the VNC from the brain switch from the left to the right side at the anterior end of the VNC. In genetic screens we identified several mutations compromising VNC asymmetry. This includes alleles of col-99 (encoding a transmembrane collagen), unc-52 /perlecan and unc-34 (encoding the actin modulator Enabled/Vasodilator-stimulated phosphoproteins). In addition, we evaluated mutants in known axon guidance pathways for asymmetry defects and used genetic interaction studies to place the genes into genetic pathways. In total we identified four different pathways contributing to the establishment of VNC asymmetry, represented by UNC-6 /netrin, SAX-3/Robo, COL-99, and EPI-1 /laminin. The combined inactivation of these pathways in triple and quadruple mutants leads to highly penetrant VNC asymmetry defects, suggesting these pathways are important contributors to the establishment of VNC asymmetry in C. elegans .